Drive signal waveform for a fluxgate - Baranov P. F. Pavel Fedorovich; Baranova V. E. Vitaliya Evgenyevna; Kolomeytsev A. A. Andrey Anatolievich; Zatonov I. A. Ivan Andreevich (2018, 2018)
Title screen